Nutritional value of foliage meal from four species of tropical trees for feeding ruminants - Rodríguez, R.; González, Niurca; Domínguez, Marbelis; Sarduy, Lucía (Cuban Journal of Agricultural Science, 2016)
In order to evaluate the nutritive value of foliage meals of moringa (Moringa oleifeira cv. Super Genius), mulberry (Morus alba Linn cv. Cubana), trichanthera (Trichanthera gigantea) and leucaena (Leucaena leucocephala cv. Perú) for feeding ruminants, their chemical composition was determined, the in vitro gas production was measured up to 96 h of incubation, and the in vitro degradability of dry matter, neutral detergent fiber and nitrogen was estimated. The gas production was measured up to 96 h, to estimate the parameters of fermentation kinetics, according to the model of Gompertz. A random block design was applied, with four incubations as repetitions and the tree species as treatments. The organic matter of moringa and leucaena surpassed 90 % and trichanthera showed low values (72 %). The crude protein was superior to 20 % in every treatment. The neutral detergent fiber varied between 30 and 50 % and the mulberry showed the lowest values. There was interaction between sampling time and treatment for gas production (P<0.001). The highest values were observed in the initial stage for moringa and mulberry, at 16 h, while the highest productions of the final stage corresponded to mulberry (96 h). The potential of mulberry fermentation tended to be higher (189.5 mL g-1 incOM), like the values of microbial efficiency factor for moringa (0.149 h-1). Mulberry and moringa showed high values of maximum speed and gas production (Vmax: 8.36 and 8.08 mL g-1 incOM h-1, respectively) and trichanthera showed the lowest value (1.29). In vitro degradability of dry matter and neutral detergent fiber were high for mulberry and low for trichanthera (P<0.001). Leucaena showed higher in vitro digestibility of nitrogen (79 %), followed by mulberry moringa and trichanthera (P<0.05). It can be concluded that, under experimental conditions, trichanthera had low potential as food, while mulberry and moringa showedhigher nutritional value than leucaena, although this last demonstrated superior potential as supplement protein degraded within the rumen.Key words: Moringa oleifeira, Trichanthera gigantea, Morus alba, Leucaena leucocephala, fermentation